Maternal Decision Making and Children’s Nutritional Status: Evidence from Indonesia - Roswita, Nadia; Dartanto, Teguh (Jurnal Ekonomi Kependudukan dan Keluarga, 2024)
Indonesia is encountering consecutive health problems caused by malnutrition. The latter poses long-term effects on children’s development. As this issue continue its prominence, using linear regression and binary logistic with time lag to analyze data from Indonesia Family Life Survey (IFLS) in 2007 and 2014 shall support the analysis of issue. Previous results from the models indicated that maternal decision-making in their share of food expenditure has a weak correlation for stunted children's experience. However, this study revealed different results. It suggested that involvement in from men in nutritional knowledge, skills, and financial backing to advance women's roles contributes to better children's nutritional outcomes. This study proved urgency to reassess and address the role of women in household decision-making to tackle issues of malnutrition in Indonesia.